The Influence of Brand Awareness, Perceived Quality, and Promotion on the Decision to Purchase a Honda Brand Automatic Motorcycle at PT. Capella Honda 88 Pekanbaru - Elgha Marenthis Purba; Mashur Fadli; Mandataris (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of brand awareness, perceived quality and promotion on purchasing decisions for Honda brand automatic motorbikes at PT. Capella Honda 88 Pekanbaru. This research method is descriptive and quantitative statistics with the analysis method in this research is multiple linear regression analysis. The sample in this study amounted to 97 respondents who were determined using purposive sampling techniques and used questionnaires as data collection. The research results show that brand awareness has a significant effect on purchasing decisions, perceived quality has a significant effect on purchasing decisions, promotion has a significant effect on purchasing decisions, brand awareness, perceived quality and promotion have a significant effect on purchasing decisions for Honda brand automatic motorbikes at PT. Capella Honda 88 Pekanbaru.